Adaptive alterations in the mesoaccumbal network after peripheral nerve injury. Issue 3 (March 2021) - Ren, Wenjie; Centeno, Maria Virginia; Wei, Xuhong; Wickersham, Ian; Martina, Marco; Apkarian, A. Vania; Surmeier, D. James
Abstract : Abstract: The nucleus accumbens (NAc) and the ventral tegmental area (VTA) are critical hubs in the brain circuitry controlling chronic pain. Yet, how these 2 regions interact to shape the chronic pain state is poorly understood. Our studies show that in mice, spared nerve injury (SNI) induced alterations in the functional connectome of D2-receptor expressing spiny projection neurons in the core region of the NAc—enhancing connections with prelimbic cortex and weakening them with basolateral amygdala. These changes, which were attributable in part to SNI-induced suppression of VTA dopaminergic signaling, were adaptive because mimicking them chemogenetically alleviated the anxiety and social withdrawal accompanying injury. By contrast, chemogenetic enhancement of activity in VTA dopaminergic neurons projecting to the medial shell of the NAc selectively suppressed tactile allodynia in SNI mice. These results suggest that SNI induces regionally specific alterations in VTA dopaminergic signaling in the NAc to promote environmental reengagement after injury. However, countervailing, homeostatic mechanisms limit these adaptive changes, potentially leading to the chronic pain state. Abstract : Supplemental Digital Content is Available in the Text.Peripheral nerve injury induces region-specific alterations in mesoaccumbens dopaminergic signaling that promote adaptive behavior. However, homeostatic mechanisms counteract these changes and enhance chronic pain.